Elevated indoleamine-2, 3-dioxygenase enzyme activity in a novel mouse model of HIV-associated atherosclerosis. (1st August 2019) - Kearns, Alison C.; Velasquez, Stephani; Liu, Fengming; Dai, Shen; Chen, Yong; Lehmicke, Gabrielle; Gordon, Jennifer; Rappaport, Jay; Qin, Xuebin
Abstract : Objective: HIV atherosclerosis and cardiovascular disease (CVD) represent a significant human health burden in the era of combination antiretroviral therapy (cART). The pathogenesis of HIV atherosclerosis is still poorly understood, due, in part, to the lack of a suitable small animal model. Indoleamine-2, 3-dioxygenase (IDO) enzyme activity is the first and rate-limiting step in tryptophan catabolism and is measured by the kynurenine to tryptophan ratio (KTR). The serum KTR is a biomarker of inflammation and has recently been implicated as an important risk factor for CVD in patients living with HIV (PLWH) who are virologically suppressed under cART. However, IDO activity in HIV-associated CVD has not been studied in mouse model before. Design: A novel mouse model of HIV atherosclerosis ( Tg26 +/− /ApoE −/− ) was generated and examined for IDO activity and atherogenesis throughout 8 weeks on a high-fat diet. Tg26 +/− /ApoE −/− mice were compared with Tg26 +/− and ApoE −/− single transgenic mice, before and during a high-fat diet. Method: Serum kynurenine, tryptophan and percentage of aortic plaque formation were measured. Additionally, levels of relevant cytokines were investigated in Tg26 +/− /ApoE −/− and ApoE −/− . Results: Tg26 +/− /ApoE −/− developed an accelerated atherosclerosis with increasing levels of KTR that were associated with plaque progression. This accelerated plaque was potentially driven by elevated levels of circulating IL-6. Conclusion: These results indicate that Tg26 +/− /ApoE −/− serve as a new mouse model for HIV-induced atherogenesis, and aid in understanding the role of tryptophan catabolism in the pathogenesis of HIV atherosclerosis/CVD. Abstract : Supplemental Digital Content is available in the text